MIPI Display Serial Interface Interoperability Tests - Rodrigues, Pedro Filipe Xavier (2018)
The increasing demand of mobile devices, with better and faster peripherals, leads to a need of developing new products based on the most recente protocols by the silicon industry companies. One of the companies with a larger role in the silicon industry is Synopsys. Synopsys is one of the biggest IP producers (Intellectual Property) in the world, offering its clients a large set of components based on the leading protocols on the market such as: USB, MIPI, HDMI, DDR, SATA, Ethernet, PCIe etc. In this thesis framework were developed two projects regarding MIPI DSI (Display Serial Interface) specification in which is proposed to use Synopsys DSI Host controller to validate the behaviour of two physical layers (PHY). One of the projects has as target test one of Synopsys new PHYs in order to validate its performance on a protocolar level. The other project refers to the protocolar validation of a client PHY that ordered Synopsys services to test it. To validate both physical layers and accomplish the project goals, both projects passed through the stages of: design development, simulations, Synthesis + P&R (Place and Route) and hardware tests.